Floristic diversity of the soil weed seedbank in boro rice fields: in situ and ex situ evaluation: Floristic diversity of the weed seedbank (Journal of the Bangladesh Agricultural University, 2018)
This study was conducted at the research fields of Agronomy Field Laboratory and in the net house of Department of Agronomy, Bangladesh Agricultural University, Mymensingh. The objective of this study was to compare the in situ and ex situ floristic diversity of soil weed seedbank in boro rice. The soil weed seedbank status was observed through weed survey at research fields and seed germination method in the net house. Five fields were selected randomly with four replications. Soil samples were collected to a depth up to 15 cm and placed in plastic pots in the net house. Weed seedlings that emerged were identified, counted and removed at 30 day intervals throughout the four months emergence period. At the same time, weed survey was done using a 0.25 m–2 quadrate. Diversity was computed by the Shannon index (H’). Under in situ condition, 31 weed species belonging to 15 families germinated and 33 weed species belonging to 17 families germinated under ex situ condition. The family Cyperaceae had the highest species richness under both in situ and ex situ conditions. The five most dominant weed species under in situ condition based on importance value were Eleocharis atroperpurea > Cyperus difformis > Echinochloa crusgalli > Monochoria vaginalis > Lindernia antipoda whereas, under ex situ condition, two new weed species, Fimbristylis miliacea and Echinochloa colonum were observed in the dominant list instead of Monochoria vaginalis and Lindernia antipoda having slightly different rank and order. The ex situ density was 2721 plants m–2, approximately four times higher than the 700 plants m–2 observed under in situ situation and similarly ex situ condition had higher Shannon Index (H’) value (H’=2.412) indicating greater diversity than in situ (H’=2.211) condition. The information obtained from the study would help determine the infestation potential of identified species, which could lead to improved management strategies.J. Bangladesh Agril. Univ. 16(3): 396–402, December 2018